Growing up laughing : my story and the story of funny - Thomas, Marlo (New York : Hyperion, 2010)
The award-winning actress shares her funny and heartwarming stories of a life filled with laughter. Woven throughout the book are her interviews with many beloved American comedians about how they, too, found the funny in their lives
"With guest appearances by Alan Alda, Joy Behar, Sid Caesar, Stephen Colbert, Billy Crystal, Tina Fey, Larry Gelbart, Whoopi Goldberg, Kathy Griffin, Jay Leno, George Lopez, Elaine May, Conan O'Brien, Don Rickles, Joan Rivers, Chris Rock, Jerry Seinfeld, Jon Stewart, Ben & Jerry Stiller, Lily Tomlin, Robin Williams, Steven Wright."
Keywords: Thomas, Marlo; Actors -- United States -- Biography; American wit and humor -- 21st century